Discourse markers in academic and non-academic writings of Thai EFL learners - Sumit Choemue; Barli Bram (Studies in English Language and Education, 2021)
The ability to use discourse markers (DMs) to create cohesion and coherence of a text is essential for EFL learners at the university level to express ideas and thoughts in various types of writing assignments, such as academic papers and reflections. Hence, this study attempted to shed more light on the use of DMs in academic and non-academic writings of Thai EFL learners. The main objective was to investigate the types, overall frequency, and differences, and similarities of discourse markers in both styles of writing. Sixty essays, consisting of 20 academic essays and 40 non-academic ones, were selected as the primary data. Academic essays were selected from the Critical Reading and Writing course of Xavier Learning Community (XLC), Thailand, while the non-academic ones were selected from the XLC English Newsletter. The data were analyzed based on Fraser’s taxonomy (2009). The results showed that 2.521 DMs distributed in five types, namely contrastive discourse, elaborative discourse, inferential discourse, temporal discourse, and spoken discourse markers, were identified in the 20 academic and 40 non-academic essays.  The most frequently used DM was elaborative discourse markers (EDM), F=1,703. This study concluded that raising awareness of DMs would assist Thai EFL learners in producing an effective and coherent piece of writing.